Do regional government green innovation preferences promote industrial structure upgradation in China? Econometric assessment based on the environmental regulation threshold effect model - Khattak, Shoukat Iqbal; Khan, Aarif Mohammad; Khan, Muhammad Kamran; Li, Chen; Liu, Jiating; Pi, Zhuojie (Frontiers in Environmental Science, 2022)
High-quality development requires to solve the problems of environmental governance and industrial structure upgrading. Innovation is the first development force in today's society. The government's green innovation preference will be reflected in the industrial structure to a certain extent. Using the threshold regression model, this paper selects the provincial panel data from 2005 to 2019, and examines the impact of government innovation preference on the industrial structure upgrading under different levels of environmental regulation. The results show that: (1) The government's green innovation preference will inhibit the upgrading of the industrial structure. (2) The "U"-shaped relationship between environmental regulation and industrial structure upgrading is significant. In this paper, considering the cooperation between "flexibility" of the government's green innovation preference and "rigidity" of environmental regulation. The "U"-shaped " type relationship between environmental regulation and industrial structure upgrading is verified with environmental regulation as a threshold variable. (3) The influence of the government's green innovation preference on the upgrading of industrial structure is heterogeneous, and the government's green innovation preference in non-resource-based regions has a stronger inhibitory effect on the upgrading of industrial structure than in resource-based regions.